2006
DOI: 10.1007/s10565-006-0033-0
|View full text |Cite
|
Sign up to set email alerts
|

The in vitro biological activity of Lepidium meyenii extracts

Abstract: The biological activity of methanolic and aqueous extracts from dehydrated hypocotyls of Lepidium meyenii (Brassicaceae, vernacular name "maca"), was studied on rat hepatocytes and human breast cancer MCF-7 cells. The extracts did not exhibit cytotoxicity in hepatocyte primary cultures up to 10 mg/ml as measured by the MTT viability test, and lactate dehydrogenase (LDH) and aspartate aminotransferase (AST) leakage. Moreover, after 72 h, extracts inhibited LDH and AST leakage from the hepatocytes. When hepatocy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0
8

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 48 publications
0
35
0
8
Order By: Relevance
“…Estudios in vitro indican que tanto los extractos metanólicos como acuosos de maca muestran actividad estrogénica en líneas celulares MCF-7 (9) , y al no haber encontrado acción en los receptores alfa estrogénicos (27) se sugiere una acción en los receptores beta de estrógenos, lo cual necesita aún ser demostrado.…”
Section: Maca Y Espermatogénesisunclassified
See 1 more Smart Citation
“…Estudios in vitro indican que tanto los extractos metanólicos como acuosos de maca muestran actividad estrogénica en líneas celulares MCF-7 (9) , y al no haber encontrado acción en los receptores alfa estrogénicos (27) se sugiere una acción en los receptores beta de estrógenos, lo cual necesita aún ser demostrado.…”
Section: Maca Y Espermatogénesisunclassified
“…En la fracción acuosa de la maca se han encontrado azucares libres, aminoácidos con alto componente de prolina, uridina, ácido málico y una fracción conteniendo glucosinolatos (9,10) , mientras que en la fase no polar hay macaenos y macamidas (ácidos grasos poliinsaturados y sus correspondientes amidas) (9) . En maca seca el contenido de macaenos oscila entre 0,09 y 0,45% (11) .…”
Section: Introductionunclassified
“…The possibility of estrogenic effects is based on the fact that Maca contains the phytoestrogen β-sitosterol 13 . Several studies, however have been unable to detect in vivo estrogenic effects 9,10,13 , although one study has reported that Maca extracts promote proliferation of MCF-7 cells, an estrogen receptor positive human breast cancer cell line 16 . Alkaloids, isothiocynates and glucosinolates are also potential active constituents of Maca 15 .…”
Section: Introductionmentioning
confidence: 99%
“…These parameters changed similarly in healthy bulls 113 and in mice following spermatogenic damage induced by malathion. 114 In vitro 115 and in vivo experiments suggest that Maca may have an estrogen-like effect, which may be related to the fertility improvement observed in female rats and mice. The uterus weight was increased in healthy mice fed with Maca, 100,116 and the rate of osteoporosis in ovariectomized rats decreased, but an increase in uterus weight related to an estrogen effect was not observed in this case.…”
Section: Pharmacology Of Lepidium Meyeniimentioning
confidence: 99%
“…118 Several reviews discuss whether the effects of Maca on the reproductive system may be due to the estrogen-like phytosterols of the hypocotyl, 28,115 but this has been refuted by other studies. 121,122 Comprehensive phytochemical and pharmacological comparisons of hypocotyls from the different color types have not been performed to date in detail.…”
Section: Pharmacology Of Lepidium Meyeniimentioning
confidence: 99%